Tindakan Genosida terhadap Etnis Rohingya dalam Perspektif Hukum Pidana Internasional - Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Faculty of Law, Universitas Wijayakusuma, 2019)
The actions taken by the Myanmar Government against its Rohingya ethnic groups have fulfilled the element that this action can be categorized as a crime of genocide. The requirement for an action can be said to be an act of genocide, if it has fulfilled elements such as mass murder, carried out systematically, discriminated against religion, and aimed at eliminating a certain minority ethnic or group. Therefore, the actions taken by the Myanmar government have fulfilled the above elements, so it can be concluded that the actions taken by the Myanmar government against the Muslim Rohingya ethnicity are international genocide crimes.Keywords: Genocide, International Criminal Law, Rohingya